Old Wine in New Bottles? Does Climate Policy Determine Bilateral Development Aid for Renewable Energy and Energy Efficiency? - Axel Michaelowa; Katharina Michaelowa (Revue Internationale de Politique de Développement)
Published by Palgrave MacmillanSince the UN Conference on Environment and Development in Rio de Janeiro in 1992 bilateral and multilateral donors have stressed that development assistance has increasingly been oriented towards climate-friendly interventions. With respect to energy aid, this should lead to a substantial increase in projects related to renewable energy and energy efficiency. Given a new database of hundreds of thousands of bilateral development assistance projects, we can assess whether such a reorientation has indeed taken place. We find that, contrary to expectations, the share of bilaterally-funded renewable energy and energy efficiency projects did not increase over the period from 1980 to 2008. This share fluctuated greatly, following the price of oil, peaking with the second oil crisis of the early 1980s. The impacts of global climate policy treaties are minor or inexistent. ‘Traditional’ renewable energies such as hydro and geothermal declined, while “new” renewables showed two peaks in the early 1980s and late 1990s. Differences between donor countries are huge. Several countries, including climate sceptics such as the US and Australia, but also the UK and Switzerland, saw a consistent decline. The self-proclaimed climate pioneers such as Germany, the Netherlands, Norway and Sweden show peaks related to both the oil crises and international climate policy. Only in Austria, Denmark, Finland and Spain can ‘new’ climate mitigation development assistance be found.